Cocoon web induced by Eruga telljohanni (Ichneumonidae: Pimplinae) in Leucauge sp. (Tetragnathidae) - Barrantes Montero, Gilbert (2017)
The hosts and cocoon webs of koinobiont-ectoparasitic wasps in the genus Eruga Townes in Townes & Townes, 1960 are known for only two species. We describe here the host spider and cocoon web of a third Eruga species: E. telljohanni Gauld, 1991. This wasp parasitizes Leucauge White, 1841 species, which are induced to construct a highly modified cocoon web, with a small flat sheet and long radii. The larval cocoon lies along the longest axis attached to the centre of the sheet. This cocoon web differs markedly from the cocoon web induced by E. gutfreundi Gauld, 1991 in Leucauge mariana (Taczanowski in Keyserling, 1881).